Influential Article Review - Examining the Nature of German Retail and Commercial Customers - Edwards, Ivan; Conner, Elena; Dennis, Kyle (Journal of Marketing Development and Competitiveness, 2019)
This paper examines retail. We present insights from a highly influential paper. Here are the highlights from this paper: Based on a unique data set of 909 defaulted retail and commercial (self-employed and SMEs) credit customers in Germany, whose original loans were made by 123 different banks, our article confirms a significant positive influence of collateral, and of amicable agreements between the debtor and the bank (redemption), on the recovery rate [1 − loss given default (LGD)]. In a further analysis of collateral, systematic biases between the realized market price and the expected market values of real estate are revealed, even though the appraisal reports should have already considered all factors influencing the value. Using valuations that were adjusted for these recognized biases, we can increase the explanatory power of the underlying models. Moreover, we compare these models to models that apply, as is common practice in the banking industry, flat haircuts to collateral values and show the superior performance of our proposed approach. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.